Inoculation with Plant Growth-Promoting Bacteria to Reduce Phosphate Fertilization Requirement and Enhance Technological Quality and Yield of Sugarcane - Poliana Aparecida Leonel Rosa; Fernando Shintate Galindo; Carlos Eduardo da Silva Oliveira; Arshad Jalal; Emariane Satin Mortinho; Guilherme Carlos Fernandes; Evelyn Maria Rocha Marega; Salatiér Buzetti; Marcelo Carvalho Minhoto Teixeira Filho (Microorganisms, 2022)
Phosphorus (P) is a critical nutrient for high sugarcane yields throughout its cultivation cycles, however, a higher amount of P becomes rapidly unavailable to plants due to its adsorption to soil colloids. Some plant growth-promoting bacteria (PGPBs) may be able to enhance P availability to plants and produce phytohormones that contribute to crop development, quality, and yield. Thus, this study aimed to evaluate leaf concentrations of nitrogen (N) and P, yield, and technological quality of sugarcane as a function of different levels of phosphate fertilization associated with inoculation of PGPBs. The experiment was carried out at Ilha Solteira, São Paulo—Brazil. The experimental design was randomized blocks with three replications, consisting of five phosphorus rates (0, 25, 50, 75, and 100% of the recommended P2O5 rate) and eight inoculations, involving three species of PGPBs (Azospirillum brasilense, Bacillus subtilis, and Pseudomonas fluorescens) which were applied combined or in a single application into the planting furrow of RB92579 sugarcane variety. The inoculation of B. subtilis and P. fluorescens provided a higher concentration of leaf P in sugarcane. The P2O5 rates combined with inoculation of bacteria alter technological variables and stalk yield of sugarcane. The excess and lack of phosphate fertilizer is harmful to sugarcane cultivation, regardless of the use of growth-promoting bacteria. We recommend the inoculation with A. brasilense + B. subtilis associated with 45 kg ha−1 of P2O5 aiming at greater stalk yield. This treatment also increases sugar yield, resulting in a savings of 75% of the recommended P2O5 rate, thus being a more efficient and sustainable alternative for reducing sugarcane crop production costs.